SYNTHESIS AND CHARACTERIZATION OF CASSAVA PEEL CARBON ACTIVATED USING ZnCl2¬ - Luki Aprilliya Setiyoningsih (Jurnal Kimia Riset, 2018)
In this study, to determine the characteristics of charcoal from the manufacture using a modification tool, and to determine the effect of system density variation. Activated charcoal is made through several stages namely, dehydration, carbonization and activation. The use of the modifikation at the carbonization stage will result in different activated charcoal. The activation proses used in chemical activation by immersing the charcoal in a ZnCl2 activator solution. The charcoal massa period used is 1:1 with the charcoal massa : the activator period. Comparison of the massa used to produce increased system density of 2%, 4%. 6%, 8%, and 10%. The activation time used in accordance with the previous study was 8 hours. The active charcoal made using the modified means is obtained for the optimum 2% effect of system density at 8 hours of activation time. Characteristic values obtained at 2% system density were 3.67% moisture content, ash content 13.5%, iod absorption 277 mg / g, and density 0.31 g / mL.Keyword:activated charcoal, modifiers, chemical activation